Analysis of Microplastics in the Digestive Tracts of Mackerel Tuna (Euthynnus affinis) and Skipjack Tuna (Katsuwonus pelamis) for SDG 14 - Masriani Masriani; Abd. Hakim Laenggeng; Fatmah Dhafir; Aan Febriawan (Journal of Current Studies in SDGs, 2026)
Objective: Marine ecosystems are increasingly threatened by microplastic pollution, which can accumulate in commercially important fish species and potentially affect human health. This study aimed to identify the characteristics and abundance of microplastics in the digestive tracts of mackerel tuna (Euthynnus affinis) and skipjack tuna (Katsuwonus pelamis) from Boneoge waters, Donggala Regency, and examine the relationship between digestive tract size and microplastic abundance. Method: A quantitative descriptive approach was employed using 30 specimens of each fish species collected from local fishermen. Digestive tract samples were digested using 10% KOH, incubated at 75°C, filtered, and observed under a binocular microscope. Microplastic abundance was expressed as particles per gram of digestive tract weight. Simple linear regression analysis using SPSS 25 was performed to evaluate the relationship between digestive tract size and microplastic abundance. Results: Three microplastic types were identified: film, fragment, and fiber, with film being dominant in both species. Total microplastic abundance reached 3.940 particles/g in mackerel tuna and 3.071 particles/g in skipjack tuna. Regression analysis showed a weak positive relationship between digestive tract size and microplastic abundance (R² = 0.137 and 0.140), suggesting that other environmental and biological factors play a greater role. Novelty: Providing the first baseline data on microplastic contamination in mackerel tuna and skipjack tuna from Boneoge waters, Central Sulawesi, and contributes to SDG 14 (Life Below Water) by strengthening evidence-based efforts to address marine microplastic pollution.